MODERN METHODOLOGY OF TEACHING THE SCIENCE OF ELECTRICAL TECHNICAL MATERIALS - Xalilova, F.A. (Educational Research in Universal Sciences, 2023)
The article discusses teaching methods based on modern educational technologies when teaching electrical materials science, which analyzes teaching technology and organization of the educational process using mixed educational technologies.